Weight loss in subjects with type 2 diabetes before and after SARS- CoV2 infection - A retrospective observational study - Roxana Adriana Stoica; Florentina Gherghiceanu (Journal of Mind and Medical Sciences)
Objectives. As weight modification during the COVID-19 pandemic was reported in several circumstances, we aimed to assess the body composition changes using bio impedance in patients with type 2 diabetes mellitus (T2DM) during this period. Materials and Methods. We conducted an observational, retrospective study, from January 2021- June 2021, in two outpatient clinics, enrolling all patients with T2DM and SARS-CoV2 infection that presented for evaluation after the infection. Blood tests (serum creatinine, urea, blood glucose, lipid profile, transaminases, HbA1c) were available before the onset of infection as well as at an interval of 1-3 months post-infection. Results. From a total of 118 patients, 101 subjects were eligible, 50.5% males. 68.6% had a mild form of SARS-CoV2 infection. There is a significant decrease in mean weight (91.9 ± 26.00 kg before and 90.00 ± 23.00 kg after infection vs. control, p<0.05), body mass index (31.80 ± 8.89 kg/m2 before and 30.47 ± 8.48 after infection vs. control, p<0.05), and visceral fat (15.00 ± 8.00% vs.14.5 ± 7.25 %) after infection. Median HbA1c increased in patients that were infected (6.5 ± 1.5 before vs 7.1 ± 1.5 after infection, non-significant) and significantly decreased in the control group (7.0 ± 2.3 % vs. 6.4 ± 1.00 %). We did not find any significant correlation between weight decrease and clinical or biological parameters in the SARS-CoV2 group. Conclusions. Weight, body mass index, and visceral fat decreased at 3-month follow-up in T2DM subjects with SARS-CoV2 infection vs controls.